Physico-chemical properties and sensory profile of durum wheat Dittaino PDO (Protected Designation of Origin) bread and quality of re-milled semolina used for its production. (15th February 2018) - Giannone, Virgilio; Giarnetti, Mariagrazia; Spina, Alfio; Todaro, Aldo; Pecorino, Biagio; Summo, Carmine; Caponio, Francesco; Paradiso, Vito Michele; Pasqualone, Antonella
Highlights: A quality characterization of Dittaino bread and starting semolina was carried out. The quality characteristics of semolina were variable, but within the legal ranges. Textural analysis evidenced moderately high values of bread hardness and chewiness. Bread contained carotenoid pigments in levels between 2.30 and 3.65 mg kg −1 . The sensory profile of Dittaino PDO bread agreed with the physico-chemical analyses. Abstract: To help future quality checks, we characterized the physico-chemical and sensory properties of Dittaino bread, a sourdough-based durum wheat bread recently awarded with Protected Designation of Origin mark, along with the quality features of re-milled semolina used for its production. Semolina was checked for Falling Number (533–644 s), protein content (12.0–12.3 g/100 g d.m.), gluten content (9.7–10.5 g/100 g d.m.), yellow index (18.0–21.0), water absorption (59.3–62.3 g/100 g), farinograph dough stability (171–327 s), softening index (46–66 B.U.), alveograph W (193 × 10 −4 –223 × 10 −4  J) and P/L (2.2–2.7). Accordingly, bread crumb was yellow, moderately hard (16.4–27.1 N) and chewy (88.2–109.2 N × mm), with low specific volume (2.28–3.03 mL/g). Bread aroma profile showed ethanol and acetic acid, followed by hexanol, 3-methyl-1-butanol, 2-phenylethanol, 3-methylbutanal, hexanal, benzaldehyde, and furfural. The sensory features were dominated by a thick brown crust, with marked toasted odor, coupled to yellow and consistent crumb, with coarse grain and well-perceivable sour taste and odor.